THE IMPROVEMENT OF MATHEMATICS LEARNING ACHIEVEMENT BY IMPROVING TEACHER PERFORMANCE CAPABILITIES THROUGH GUIDANCE AND SUPERVISION BY PRINCIPALS - Rohaimi Rohaimi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Mathematics is a study that has an abstract object and is built through a process of deductive reasoning which the truth of a concept is obtained as a logical consequence of the truth previously accepted so that the relationship between concepts in mathematics is very strong and clear. In the implementation of the teaching and learning process of Mathematics in elementary schools, the various methods are used and adapted to the material presented by educators or teachers. It is intended if problems occur and difficulties in learning Mathematics will be easily solved. In this case the writer used the Guidance and Supervision by Principal's method. This school action research consisted of two cycles, namely cycle I and cycle 2. Where in each cycle consisted of action planning, action implementation, observation and reflection. This research was conducted in sixth grade students of SDN 137 Pekanbaru. The analysis technique was carried out qualitatively and quantitatively. This research aimed to improve student achievement in learning mathematics through guidance and supervision by principal. The results showed that with the supervision by principals had increased by 30%, the student learning outcomes averaged 62.66 to 85.33 by increasing student learning achievement. Thus, it can be concluded that with the guidance and supervision by principals can improve student learning achievement. Therefore, it is hoped that it will always improve the ability of its performance in learning so that the quality of education in schools increases.